Kajian DRPs dan pola peresepan pada pasien rawat inap anak dengan asma - Dyah Anggraeni Budhi Pratiwi; Novita Anggraini; Nur Aeni (STIKes Surya Global Yogyakarta, 2022)
The incidence of drug-related problems (DRPs) is very common occur in pediatric inpatients where treatment must be prioritized because their physiological conditions are not yet perfect so metabolism and drug absorption cannot be equated. The risk of developing DRPs results in a decrease in the patient's quality of life, increases the rate of death and disability and increases costs. Asthma is a chronic disease, the prevalence of asthma in children is high enough that it requires serious attention. In Indonesia, the prevalence of asthma in elementary school children (0-14 years) is 9.6%. This study aims to identify drug related problems and determine treatment patterns in pediatric patients with asthma at X Hospital. This research was a non-experimental study conducted with a descriptive design through retrospective data retrieval of the medical records of children with asthma who were hospitalized in January-July 2017 at X hospital. DRPs and treatment patterns were assessed from the patient's medical record data and then analyzed using percentages. DRPs were entered in bullet points while treatment patterns were in the table. The results of this study were the class of drugs used. Corticosteroids, beta-2 agonists, beta-2 agonists and anticholinergic combinations, beta-2 agonist combinations with corticosteroids, antihistamines, antihistamine and decongestant combinations and methylxanthine. Types of drugs used are salbutamol, procaterol, dexamethasone, methylprednisolone, triamcinolone, budesonide, aminophylline, and a combination of albuterol and ipratropium bromide. The results of the DRPs study were, that there was no indication that there was no treatment, drugs with inappropriate indications in 50%, the wrong drug was 66.6%, the dose was too high at 61.1%, drug interactions amounted to 22.2%, and non-compliance does not exist.